Development of Drip Irrigation Monitoring and Control System Model Based on the Internet of Things Using Android Applications - Walid, Miftahul; Horiyah, Horiyah; Rofiuddin, Rofiuddin; Susilo, Purnomo Hadi; Wahyudi, Muhammad Hasan (INTENSIF: Jurnal Ilmiah Penelitian dan Penerapan Teknologi Sistem Informasi, 2025)
Background: Efficient water management is crucial for sustainable agriculture, particularly in regions with limited water resources. Drip irrigation systems, when integrated with the Internet of Things (IoT), offer a promising solution to optimize water usage and enhance agricultural productivity. Objective: This study aims to develop an IoT-based drip irrigation system to improve water efficiency and support small-scale farmers by providing a cost-effective and adaptable solution. Methods: The system employs multiple sensors to monitor key environmental parameters, including soil moisture, air temperature, and water levels in the tank. The collected data is transmitted to the ThingSpeak cloud platform via an Android application for real-time monitoring and control. Performance metrics such as sensor reaction time, solenoid valve response time, and pump response time were analyzed to evaluate system effectiveness. Results: Experimental findings show that the system effectively monitors and regulates irrigation, with an average sensor reaction time of 2.95 seconds, a solenoid valve response time of 2.75 seconds, and a pump response time of 2.3 seconds. The system successfully automates irrigation, ensuring optimal water usage. Conclusion: The IoT-based drip irrigation system enhances water resource management, increases crop yield, and reduces operational costs. While the system demonstrates high efficiency, further research could focus on scalability, integration with predictive analytics, and adaptation to different crop types and environmental conditions.